The Effect of Neoprene Knee Brace with Hinge on Dynamic Balance in Osteoarthritis Knee - Anggriani, Atika Febri; Fatati, Muhibbah; Husna, Harnintya Tri (Poltekkes Kemenkes Jakarta I, 2025)
Background: Osteoarthritis of the knee is a degenerative joint disease that often causes pain, activity limitations, and balance disorders, particularly dynamic balance. One conservative approach to reducing symptoms and improving knee joint stability is the use of neoprene knee brace with hinges to provide compression and lateral-medial support, as well as enhance proprioception and neuromuscular control, all contributing to improved dynamic balance. Aims: To determine whether there is an effect of using a neoprene knee brace with hinge on dynamic balance in patients with knee osteoarthritis. Methods: This research method is quasi-experimental with a one-group pre-test and post-test design. The research sample consisted of 18 women aged 45-60 years who were selected using purposive sampling techniques based on inclusion and exclusion criteria. This study used the Time Up and Go Test to measure dynamic balance. Data normality was checked using the Shapiro-Wilk test, and statistical analysis was performed with a Paired Sample T-test. Results: Data analysis using a paired sample t-test showed a p-value of 0.000, indicating a significant difference between the pre-test and post-test scores. The average TUG test time before brace use was 16.60 seconds and after the intervention was 10.06 seconds, a difference of 6.54 seconds. Conclusion: The use of a neoprene knee brace with hinge has a significant effect on improving dynamic balance in patients with knee osteoarthritis, and can be an effective non-surgical intervention option in conservative treatment.